Comparative Performance Evaluation of the Shelters at Complutum, a Roman Archaeological Site in Spain. (3rd March 2020) - Cabello-Briones, Cristina
ABSTRACT: The Roman city of Complutum (Alcala de Henares, Spain) conserves archaeological remains declared of cultural interest at an international level. The site presents two areas which are currently covered, the House of Hippolytus and the House of the Griffins, both with exceptional decorative programmes. Shelters are commonly considered the most suitable preventive conservation option for exposed archaeological sites, as they are able to reduce the impact of direct sunlight and rainfall. However, shelters may not fully protect a site and active decay has been often documented on covered remains. An extensive monitoring programme based on temperature, relative humidity, and light readings inside and outside the shelters has been undertaken over the course of a year (2018–2019) to evaluate the suitability of sheltering and the performance of the two types of covers from the point of view of the preservation of the remains.